2022
DOI: 10.3390/recycling7040043
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Comparison of Natural and Recycled Aggregates Using LCA

Abstract: Recycled aggregates (RAs) have been playing an important role in replacing natural aggregates (NAs) in concrete production, thereby contributing to a reduction in the extraction of natural resources and the promotion of a circular economy. However, it is important to assess the global impacts of this replacement, in both environmental and economic terms. In this study, an overview of the impacts of the production of natural and recycled aggregates is presented, using the life cycle assessment (LCA) methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…It is worth noting that numerous LCA studies (e.g. de Brito et al, 2022;Dias et al, 2022) have demonstrated discrepancies in natural resource consumption between NAC and RAC, as evident by indicators such as abiotic depletion. However, the current study's calculation Fabric filter à Fresh-water is pumped from a river by electricity.…”
Section: Assessment Results and Interpretationmentioning
confidence: 99%
“…It is worth noting that numerous LCA studies (e.g. de Brito et al, 2022;Dias et al, 2022) have demonstrated discrepancies in natural resource consumption between NAC and RAC, as evident by indicators such as abiotic depletion. However, the current study's calculation Fabric filter à Fresh-water is pumped from a river by electricity.…”
Section: Assessment Results and Interpretationmentioning
confidence: 99%
“…Grabois et al [18] analyzed the performance of RCA mortars through different impact categories and observed that high levels of Natural Aggregate (NA) replacement by RCA was less detrimental to the environment and that the RCA evaluation was strongly influenced by long transport distances. Transport distance is also mentioned by Dias et al [19] as a crucial parameter in RCA LCA.…”
Section: Introductionmentioning
confidence: 84%
“…The LCA approach is a methodology widely used in waste management studies to find the best option in terms of environmental and economic impact. In [8], the authors used LCA results from different sources to compare the production of natural and recycled aggregates for concrete. The authors considered the following parameters to perform the comparison: global warming potential, non-renewable energy consumption, and the cost of 1 tonne of natural and recycled aggregates from cradle to gate.…”
Section: Lca Studiesmentioning
confidence: 99%